1993
DOI: 10.1093/genetics/135.4.1077
|View full text |Cite
|
Sign up to set email alerts
|

A new biological rhythm mutant of Drosophila melanogaster that identifies a gene with an essential embryonic function.

Abstract: To identify components of a circadian pacemaker output pathway, we have sought Drosophila mutations that alter the timing of eclosion but do not perturb circadian period or the expression of the activity rhythm. A mutant named lark has been identified, for which daily peaks of eclosion occur abnormally early while populations are synchronized to either light/dark or temperature cycles. The temporal phasing of locomotor activity in lark mutants, however, is entirely normal, as is the free-running period of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…RBM4 protein is an RNA binding protein that contains two classical RNA recognization motifs (RRM) and one zinc finger domain. RBM4, a homolog of silkworm LARK, was first identified in Drosophila melanogaster , and the LARK mutant resulted in early eclosion [ 37 ]. We previously found that LARK can bind the G4 structure in the promoter region of a variety of genes, as well as the RNA G4 structure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…RBM4 protein is an RNA binding protein that contains two classical RNA recognization motifs (RRM) and one zinc finger domain. RBM4, a homolog of silkworm LARK, was first identified in Drosophila melanogaster , and the LARK mutant resulted in early eclosion [ 37 ]. We previously found that LARK can bind the G4 structure in the promoter region of a variety of genes, as well as the RNA G4 structure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…(f ) De¢nitively out One of the biggest challenges in circadian biology is to link what we know about the circadian pacemaker with what we see as rhythmic phenotypes. Several genes have emerged as part of the clock output; one is lark, a gene whose product encodes an RNA-binding protein that is required for rhythmic eclosion but not adult locomotor behaviour (Newby & Jackson 1993;McNeil et al 1998). LARK protein cycles in abundance in a restricted number of neurons in the central nervous system (CNS) and the ventral nervous system (VNS) of late pupae, and colocalizes with a neuropeptide CCAP, which plays a role in insect ecdysis (see McNeil et al 1998, and references therein).…”
Section: (E) Somewhere In the Loopsmentioning
confidence: 99%
“…The adult eclosion rhythm of Drosophila melanogaster , a model organism for genetic dissection of the circadian clock, is also entrained by the LD cycle (Newby & Jackson 1993; Qiu & Hardin 1996). One of the characteristics of this rhythm is that eclosion is not restricted to a narrow time period but rather appears as a broad peak covering the light period of a 12 h light, 12 h dark cycle (LD 12 : 12) at 25°C (Qiu & Hardin 1996).…”
Section: Introductionmentioning
confidence: 99%